Appropriation of English as an international lingua franca (EILF) in ASEAN - Songyut Akkakoson; Loi, Chek Kim (2018)
Given that present-day English plays an important role as an international lingua franca in the ASEAN region far outside the so-called Inner Circle, a question has been asked whether the language is still the sole property of people in native settings, or whether it has already been shared by a vast majority of speakers in particular outer- and expanding-circle countries where English is utilised as a second language and a foreign language by users of diverse linguistic and cultural backgrounds. This concern voices a call for increased attention to ESL and EFL learners’ language appropriation and their identity formation to see the relationships between these learners’ sense of self and their positioning with respect to English. This article provides insight into the theoretical background of a study which was designed to explore Thai postgraduates’ opinions or feelings about their taking ownership of English as an International Lingua Franca in ASEAN and how they view themselves in relation to the language. A qualitative approach was applied, using open-ended interview questions to obtain the data from the participants. 44 postgraduate students who enrolled on existing courses of the two English-related programmers were taken as a sample group. The paper starts with a discussion of the present status of English across the globe including English as an International Language, World Englishes and English as an International Lingua Franca in ASEAN. It, then, moves on to a description of how a language and its learners’ culture and identity formation are related. It ends with a brief review of concern over linguistic imperialism and ideas about how the ownership of the language has been taken.